Analisis Hukum Qanun Aceh terhadap Pelaku Qadzf Ikhtilath - Nurfyana Narmia Sari; abdul halim Talli; kurniati Kurniati (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2021)
Qadzf ikhtilath jinayah an act that is set up in Aceh Qanun No. 6 of 2014 concerning jinayah, Qadzf ikhtilath are accusing others of committing ikhtilath or two-pair, and making out. The type of research used is library research (library research) Accusing others of committing acts of ikhtilath, including intentional acts because they have intended and done those acts. Although berikhtilat is forbidden in religion but do not accuse others. Exxon ikhtilath in Aceh in accordance with canon law if it could not prove the act of the accused offender qadzf will be chargedcaning and a fine of 30 times the gold. The accuser is also obliged to bring 4 witnesses at the same time if the accuser is unable to bring witnesses then the accuser will also be under the law of ta'zir. Witnesses who must be present must not come alone because they will be declared as accusers so the witnesses who must be present must come together. And the perpetrator of qadzf ikhtilath will lose his sentence if the accused person admits his robbery, so the one who gets the punishment is the person who is accused because he has admitted his deeds. To avoid the act of qadzf ikhtilath has been regulated in Law No.6 of 2014 on Crimes as a warning to the perpetrators not to hurt others and protect the community who are the victims of the accusation.